Atomic Layer Deposition of Functional Layers for on Chip 3D Li‐Ion All Solid State Microbattery. Issue 2 (11th October 2016) - Létiche, Manon; Eustache, Etienne; Freixas, Jeremy; Demortière, Arnaud; De Andrade, Vincent; Morgenroth, Laurence; Tilmant, Pascal; Vaurette, François; Troadec, David; Roussel, Pascal; Brousse, Thierry; Lethien, Christophe
Abstract : Nowadays, millimeter scale power sources are key devices for providing autonomy to smart, connected, and miniaturized sensors. However, until now, planar solid state microbatteries do not yet exhibit a sufficient surface energy density. In that context, architectured 3D microbatteries appear therefore to be a good solution to improve the material mass loading while keeping small the footprint area. Beside the design itself of the 3D microbaterry, one important technological barrier to address is the conformal deposition of thin films (lithiated or not) on 3D structures. For that purpose, atomic layer deposition (ALD) technology is a powerful technique that enables conformal coatings of thin film on complex substrate. An original, robust, and highly efficient 3D scaffold is proposed to significantly improve the geometrical surface of miniaturized 3D microbattery. Four functional layers composing the 3D lithium ion microbattery stacking has been successfully deposited on simple and double microtubes 3D templates. In depth synchrotron X‐ray nanotomography and high angle annular dark field transmission electron microscope analyses are used to study the interface between each layer. For the first time, using ALD, anatase TiO2 negative electrode is coated on 3D tubes with Li3 PO4 lithium phosphate as electrolyte, opening the way to all solid‐state 3D microbatteries. The surface capacity is significantly increased by the proposed topology (high area enlargement factor – "thick" 3D layer), from 3.5 μA h cm −2 for a planar layer up to 0.37 mA h cm −2 for a 3D thin film (105 times higher). Abstract : Atomic layer deposition of four thin films is performed on 3D scaffold exhibiting an area enhancement factor value close to 55. Transmission electron microscope and synchrotron X‐ray nanotomography analyses are combined to study the interfaces. The areal capacity of a TiO2 electrode move from 3.5 μA h cm −2 for planar thin film up to 0.37 mA h cm −2 for a 3D layer coated with conformal solid electrolyte Li3 PO4 .